How investor sentiments spillover from developed countries to developing countries? - Muhammad Zia Ur Rehman; Zain ul Abidin; Faisal Rizwan; Zaheer Abbas; Sajjad Ahmad Baig (Cogent Economics & Finance, 2017)
This study aims to analyse the wage differentials between the Brazilian tourism and non-tourism service sectors. The statistics originate from micro-data for the year of 2012, published by the National Household Sample Survey, and released by the Brazilian Institute of Geography and Statistics. Using an econometric model, based on an updated version of the Oaxaca-Blinder decomposition, it was possible to measure wage differentials between workers in both sectors. We report that returns in the non-tourism sector were higher than that of the tourism sector, and also conclude that in the Brazilian service sector, the wage gap is derived from differences in worker characteristics, to the detriment of the tourism industry. Moreover, variables such as schooling and age proved to have weight for the explanation of the wage differential, the latter being taken as a proxy of experience in the labour market.
Keywords: 330; sentiments; investor sentiment index; STURN; RSI; MFI; IBOR; foreign markets